Ռազմաքաղաքացիական հարաբերությունների փոխակերպումը հետսառըպատերազմյան Թուրքիայում - Գասպարյան Աբրահամ (YSU Journal of International Affairs, 2015)
Civil-military relations in Turkey have been an everlasting debate since the foundation of the republic in 1923. In order to maintain political order and protect these institutions, the military found it necessary to intervene five times in 1960, 1971, 1980, 1997 and 2007. This article looking at the period between 1997 and 2007 and analyzing the civil-military dynamics in Turkey in the context of National Security policy making process and in the framework of EU integration process. Furthermore, in terms of the roles and missions of the military in Turkey, the article discussing the problems of “civilianization” of army institution, the specific features of National Security discourse in that country as an obstacle on the road of consolidating democracy.